Identification of a rare variant in TNNT3 responsible for familial dilated cardiomyopathy through whole-exome sequencing and in silico analysis - Motahareh Jadidi; Vida Babaali; Kolsoum InanlooRahatloo; Najmeh Salehi; Reza Mollazadeh (European Journal of Medical Research)
Abstract Background Dilated cardiomyopathy (DCM) is a prevalent etiology of heart failure, distinguished by the gradual and frequently irreversible myocardial muscle impairment. Roughly 50% of DCM occurrences stem from hereditary rare variants. In this study, our aim was to identify the genetic cause of DCM in a pedigree with several affected individuals across four generations. Methods Whole exome sequencing was performed on the proband, with variants filtered and analyzed using in silico tools. Co-segregation analysis was conducted using Sanger sequencing. Protein structure modeling and protein–protein interaction evaluations were performed using AlphaFold3 and HADDOCK2.4, respectively. Results We identified a missense rare variant in the TNNT3 gene, leading to the p.Glu125Gly alteration in the Troponin T3 (TNNT3). This rare variant is strongly implicated as the causative factor for DCM in the pedigree. Several key factors underscore its significance: the rare variant co-segregates with the disease in the pedigree, is absent in 850 control samples, alters a conserved amino acid, is predicted to detrimentally affect protein function, and results in structural changes. Conclusions Our findings suggest that TNNT3 rare variants can induce DCM by weakening the binding energy between TNNT3 and Tropomyosin (TPM), leading to functional deficiencies in muscle contraction, as demonstrated by our structural modeling and docking studies. Troponin T is essential for the proper contraction of striated muscles and is related to cardiac development. Bioinformatics investigations have elucidated the involvement of TNNT3-related pathways, notably the Striated Muscle Contraction pathway and Cardiac Conduction. TNNT3 resides within loci previously implicated in cardiomyopathy. Given its crucial role in muscle contractile function, rare variants in TNNT3 hold the potential to be a significant contributing factor in the pathogenesis of DCM. A wealth of literature substantiates the correlation between troponin T and cardiac disorders. Our findings further corroborate this association.